Determinação de áreas impermeáveis por meio de ferramentas de geoprocessamento - Moreira, Pedro Augusto Gonzaga (2021)
The accelerated urbanization process associated with the government’s lack of planning generates environmental, social and economic impacts. Inherent in the urbanization process, impervious surface coverage appears as one of the main factors that generate these impacts, even becoming an indicator not only of the degree of urbanization, but also of environmental quality. goiânia was planned for 50 thousand inhabitants, however, today it has more than 1.2 million inhabitants. Therefore, it is justifiable to determine the percentage of impermeable areas in the urban perimeter of the city of Goiânia, state of Goiás, Brazil, as well as to determine the quality of drainage in the census sectors, generating a product that supports decision-making by of public managers. For that, we used the object-oriented classification technique implemented in the free InterImage software. The drainage quality map was generated by crossing the impermeable areas, Topographic Wetness Index (TWI) map and access to micro-drainage equipment. The result of the final classification was Kappa index 85%, considered excellent. The regions of the study area with the highest waterproofing rates were: central and south with 73 and 71%, respectively. The other regions had waterproofing rates close to 50%. However, it should be noted that the northern region is 35% urbanized, and according to the Goiânia risk map, this region should be preserved. In relation to the InterImage software, one should point out its limitation in relation to the maximum amount of pixel it can process. The urban drainage quality map generated identified that approximately 70% of the study area is found to be very unfavorable and unfavorable, a fact directly related to the current high degree of waterproofing of the study area